2007
DOI: 10.1002/ccd.21075
|View full text |Cite
|
Sign up to set email alerts
|

Differences in right and left ventricular remodeling after transcatheter closure of atrial septal defect among adults

Abstract: "Shrinkage" of the RV and "expansion" of the LV occurred soon after the procedure, even in elderly patients. Device closure of ASDs caused rapid improvement of LV function, but RV function underwent transient deterioration, probably due to delayed changes in RV ventricular mass in the face of acute volume reduction in this aged cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
42
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 23 publications
11
42
0
1
Order By: Relevance
“…The unloading of the right ventricle may cause a decrease in RV function immediately after the procedure [2]. This phenomenon might also be related to myocardial compliance of the right ventricle [29]. We found that tissue Doppler-derived left ventricular Tei index was significantly decreased during the follow-up period.…”
Section: Myocardial Performance Indices Of Rv and LVmentioning
confidence: 93%
“…The unloading of the right ventricle may cause a decrease in RV function immediately after the procedure [2]. This phenomenon might also be related to myocardial compliance of the right ventricle [29]. We found that tissue Doppler-derived left ventricular Tei index was significantly decreased during the follow-up period.…”
Section: Myocardial Performance Indices Of Rv and LVmentioning
confidence: 93%
“…Several studies and our own experience have demonstrated clinical benefits and positive right-heart remodeling, with reduction of the right ventricular end-diastolic diameter. (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) However, few studies were published considering geriatric patients, who older than 70 years. (18)(19)(20)(21) In this aged population, not only catheter closure of ASD but also surgical closure has been reported very limited experiences, little data are published on functional results.…”
Section: Introductionmentioning
confidence: 99%
“…These values approached to those in healthy controls (0.39±0.04 a year after vs. 0.38±0.04 in healthy controls, P=ns) indicating that closure of ASD improves global RV function [41]. Wu et al [42] reported that while LV Tei index improved soon after the procedure, RV Tei index worsened until 1 month after the procedure, then recovered by the 3-month follow-up visit indicating that Device closure of ASDs caused rapid improvement of LV function, but RV function underwent transient deterioration, probably due to delayed changes in RV ventricular mass in the face of acute volume reduction [42]. Our study showed non-significant difference between RV Tei index 1year after ASD closure and normal values.…”
Section: Discussionmentioning
confidence: 68%